2014
DOI: 10.1016/j.eats.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Lamina-Specific Double-Row Fixation for Large Delaminated Rotator Cuff Tears

Abstract: Delamination is a commonly observed finding at the time of rotator cuff repair, but few studies have described the surgical techniques used for delaminated rotator cuff tears (RCTs) or their clinical outcomes. We developed a technique using a combination of a double row and an additional row, which we call lamina-specific double-row fixation, for large delaminated RCTs. The lamina-specific double-row technique is performed using an additional row (lamina-specific lateral row) of suture anchors placed between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 13 publications
(15 reference statements)
0
16
0
Order By: Relevance
“…Based on previous reports regarding the clinical results of repairs of delaminated rotator cuff tears, the clinical results of the series in which each layer was separately repaired have been better compared with those in which both layers were repaired together as a single layer 10, 16, 22, 23. In other reports, rotator cuff tears with delamination are often described as having a high rate of postoperative tear, which occurs at the articular side 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous reports regarding the clinical results of repairs of delaminated rotator cuff tears, the clinical results of the series in which each layer was separately repaired have been better compared with those in which both layers were repaired together as a single layer 10, 16, 22, 23. In other reports, rotator cuff tears with delamination are often described as having a high rate of postoperative tear, which occurs at the articular side 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Delamination is a commonly observed finding at the time of rotator cuff repair, 9 , 10 and clinical studies have reported it as a negative prognostic factor in rotator cuff healing. 11 The repair of delaminated tears is more complex than that of nondelaminated tears, mainly because the margin of the inferior (articular-side) layer is usually more retracted than that of the superior (bursal-side) layer.…”
Section: Discussionmentioning
confidence: 99%
“…The operative technique of ALSDR has been described in detail previously (Figure 1). 22 The operative indication of ALSDR was as follows: The treating surgeon evaluated delamination by pulling the torn superior and inferior layers laterally to the footprint using a tendon grasper with a 7-mm bite. If the edge of the inferior layer could be grasped and pulled laterally to the footprint with the grasper, we regarded this inferior layer as thick and tough tissue.…”
Section: Methodsmentioning
confidence: 99%
“…11,13,25,35 Therefore, we developed a technique using a combination of a double row and an additional row, which we call arthroscopic lamina-specific double-row fixation (ALSDR), for the treatment of large-sized delaminated RCTs in active patients. 22…”
mentioning
confidence: 99%